The Banality of Environmental Evil: From the Irrational Alienation Toward Democratic Deliberation in Environmental Law Formation - Souza, Leonardo da Rocha de (2015)
This study discusses the emergence of environmental banal evil in the complex societies since the concept of the banality of evil developed by Hannah Arendt in the book "Eichmann in Jerusalem". From this, proposes to develop a proactive action towards environmental protection, away from society in a neutral position in this area, as this neutrality creates an irrational alienation. Will use the deductive method and the indirect documentation of research technique. As a result, we intend to demonstrate that individuals must be willing to consciously democratic participation by developing an ability to think and formulate rational arguments on this subject in the public sphere.